Genotypic diversity of environmental Cryptococcus neoformans isolates from Northern Portugal. Issue 2 (15th July 2013) - Ferreira, Ana Sofia; Sampaio, Ana; Maduro, Ana Paula; Silva, Inês; Teles, Fernando; Martins, Maria da Luz; Inácio, João
Summary The Cryptococcus neoformans/C. gattii species complex members are the main agents of systemic cryptococcosis. This disease is believed to be acquired from the environment via fungal cell inhalation. Often, isolates recovered from environmental and clinical sources have proven to be genotypically similar. We assessed the occurrence of C. neoformans and C. gattii in environmental substrates collected in a Portuguese region. Twenty‐eight isolates were identified as C. neoformans – five from decaying Eucalyptus leaves and 23 from domestic pigeon droppings. The isolates were genotyped using a URA5‐RFLP approach. The C. neoformans VNIV (53.6%, n = 15) and VNI (32.1%, n = 9) genotypes were abundantly present among environmental isolates. The hybrid VNIII (14.3%, n = 4) genotype was underrepresented and the VNII was not found. Cryptococcus gattii was also not found although some isolates yielded a positive canavanine–glycine–bromothymol blue test.